Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.70
|View full text |Cite
|
Sign up to set email alerts
|

Lower bounds for text indexing with mismatches and differences

Abstract: In this paper we study lower bounds for the fundamental problem of text indexing with mismatches and differences. In this problem we are given a long string of length n, the "text", and the task is to preprocess it into a data structure such that given a query string Q, one can quickly identify substrings that are within Hamming or edit distance at most k from Q. This problem is at the core of various problems arising in biology and text processing.While exact text indexing allows linear-size data structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…This list does not include lower bounds that can be obtained as consequences of these lower bounds (e.g., through reductions). In addition, the pointer machine lower bound frameworks have been applied to some string problems [8,7,18] as well as to the I/O model (a.k.a the external memory model) [22,9]. In fact, the author has shown that under some very general settings, it is possible to directly translate a pointer machine lower bound to a lower bound for the same problem in the I/O model [1].…”
Section: Static Lower Boundsmentioning
confidence: 99%
“…This list does not include lower bounds that can be obtained as consequences of these lower bounds (e.g., through reductions). In addition, the pointer machine lower bound frameworks have been applied to some string problems [8,7,18] as well as to the I/O model (a.k.a the external memory model) [22,9]. In fact, the author has shown that under some very general settings, it is possible to directly translate a pointer machine lower bound to a lower bound for the same problem in the I/O model [1].…”
Section: Static Lower Boundsmentioning
confidence: 99%
“…More efficient solutions for k = 1 are known (see [10] and references therein). Cohen-Addad et al [31] showed that, under SETH, for k = Θ(log n) any indexing data structure that can be constructed in polynomial time cannot have O(n 1−δ ) query time, for any δ > 0. They also showed that in the pointer machine model, for k = o(log n), exponential dependency on k either in the space or in the query time cannot be avoided (for the reporting version of the problem).…”
Section: Other Related Workmentioning
confidence: 99%
“…There are conditional lower bounds for approximate similarity search under edit distance based on the strong exponential hypothesis (SETH). In short, as the approximation factor c → 1, the strong exponential time hypothesis implies that any approximate similarity search algorithm with polynomial preprocessing time must approach linear search time [29,57].…”
Section: Related Workmentioning
confidence: 99%
“…Recent work in fine-grained complexity has begun to explain this difficulty: achieving significantly better than linear search time would violate the strong exponential time hypothesis. [4,29,57] However, these queries can be relaxed to approximate similarity search queries. For an approximation factor c, we want to find a database item that is at most a c factor less similar than the most similar item.…”
Section: Introductionmentioning
confidence: 99%